2023
DOI: 10.3390/life13091912
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Aspects of a New Probiotic Concept—A Pilot Study

Nina Okuka,
Verena Schuh,
Ulrike Krammer
et al.

Abstract: Several studies report the important role of an altered gut microbiota in the development of obesity, highlighting the potential use of probiotics in the treatment of obesity. The aim of this study is to investigate the effect of a novel probiotic approach on the expression of specific miRNAs and mRNAs associated with obesity in combination with the hypocholesterolemic octacosanol. Twenty overweight/obese women participated in a randomized, placebo-controlled, double-blind study and were randomly divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The pilot study included 20 participants for epigenetic and lipid profile analysis in the previous study by the authors. 14 The current study presents extended results for lipid parameters for a larger number of participants. Moreover, we noticed a significant time effect for weight and BMI ( F = 14.34, p < 0.001, η 2 = 0.242; F = 15.99, p < 0.001, η 2 = 0.258; respectively).…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…The pilot study included 20 participants for epigenetic and lipid profile analysis in the previous study by the authors. 14 The current study presents extended results for lipid parameters for a larger number of participants. Moreover, we noticed a significant time effect for weight and BMI ( F = 14.34, p < 0.001, η 2 = 0.242; F = 15.99, p < 0.001, η 2 = 0.258; respectively).…”
Section: Resultsmentioning
confidence: 52%
“…25 These data could explain the improvement of IL-6 levels in obese women in our study, which in turn could decrease CRP levels as recently suggested. 39 Although we observed a decrease in TNF-α expression in the intervention group in our previous study with a smaller number of subjects, 14 no significant changes in TNF-α levels were observed after the intervention. In two studies conducted by Kopp et al (multi-strain Lactobacillus and Bifidobacterium probiotic, omega-3 fatty acids and vitamin D, 8 weeks) and Gøbel et al ( Lactobacillus salivarius , 12 weeks), statistically significant changes of TNF-α levels were not observed.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation